I classici in partibus infidelium. Carena traduttore tra felicità e peccato - Francesco Padovani; Jacopo Parodi (Status Quaestionis, 2024)
Carlo Carena was the translator of Einaudi classical texts for decades. Despite his assertion that the translated work matters more than the translator, his choice of authors to translate (mainly Plutarch and Augustine) outlines the development of a very personal trajectory. In fact, ancient authors are read in the light of a restless Christianity, nourished by the reading of Augustine, Montaigne, and Pascal. This essay investigates the first half of Carena’s production as a translator (1956-1992), highlighting the cultural project that ambitiously integrates the ancient world and the modern world in the name of profound ethical and spiritual values. Through the translation of ancient biographies, the translator also speaks of himself and his worldview.